Analisis Pengaruh Corporate Governance, Struktur Kepemilikan, Dan Cash Holding Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Yang Listing Di Bursa Efek Indonesia Tahun 2019-2021 - Roni Tandi Tuku; Wilma Dian Ardiyanti; Winta Panimba (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research aims to examine the influence of corporate governance (board size), ownership structure (managerial ownership, foreign ownership, and family ownership), and cash ownership on firm value as measured using Tobins Q. This research uses the Ordinary Least Square (OLS) regression test on Tobins Q using manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. The results of this research show that the cash holding variable has a significant negative effect on company value. Meanwhile, other variables such as corporate governance, namely the size of the board of directors, ownership structure in foreign, family and managerial ownership have a significant positive influence on company value.